GREEN BANKING TERHADAP PROFITABILITAS BANK UMUM SYARIAH DI INDONESIA - Nur Wahyu Ningsih; Hanif Hanif; Fatullah Iqbal (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
Islamic commercial banks are sharia banks which in their activities provide services in payment traffic. Islamic commercial banks can act as foreign exchange banks and non-foreign exchange banks. Foreign exchange banks are banks that can carry out overseas transactions or those related to foreign currencies as a whole such as overseas transfers, overseas collections, opening letters of credit and so on. The research objective is to determine that green banking affects the profitability of Islamic Commercial Banks in Indonesia and the concept of green banking from an Islamic perspective. This type of research is quantitative with a statistical descriptive approach. The research methodology used in this research is the method of documentation and literature study. The data used in this study are secondary data, namely the annual reports of Islamic Commercial Banks for the period 2015-2018. The dependent variable in this study is Net Profit Margin (NPM). While the independent variable is Green banking indicators. The data analysis method used is simple linear regression, coefficient of determination (R2), and hypothesis testing, namely the partial test (Y), the data processing used is the SPSS 21 program. The results show that green banking has a positive effect on the profitability of Islamic Commercial Banks in Indonesia. . From an Islamic perspective, all Green Banking indicators are in accordance with an Islamic perspective as well as reinforcing arguments about protecting nature and preventing natural damage.